Optimization of a Brayton external combustion gas-turbine system for extended range electric vehicles - Bou Nader, Wissam S. (2018)
Significant research efforts are considered in the automotive industry on the use of low-carbon fuels in order to reduce the emissions and improve the fuel economy of vehicles. Some of these fuels, such as the solid fuels for example, are only compatible with external combustion machines. These machines are only suitable for electrified powertrains relying on electric propulsion, in particular the extended-range-electric-vehicles with series hybrid powertrain configuration where fuel consumption strongly relies on the energy converter efficiency and power density. This paper investigates the fuel savings potential of these vehicles using a Brayton external combustion gas-turbine system as energy converter substitute to the conventional internal combustion engine. An exergo-technological explicit analysis is conducted to identify the best system configuration. A downstream-intercooled reheat external combustion gas-turbine (DIRe-ECGT) system is prioritized, offering the highest efficiency among the investigated systems. An extended-range-electric-vehicle model is developed and energy consumption simulations are performed on the worldwide-harmonized light vehicles test cycle. Fuel consumption simulation results are compared to a reference extended-range-electric-vehicle using an engine auxiliary-power-unit. Results show 6%–11.5% of fuel savings with the prioritized DIRe-ECGT auxiliary-power-unit as compared to the reference model, depending on the battery capacity and the trip distance.